PRINSIP-PRINSIP MUJADALAH DALAM AL-QUR'AN DAN MANIFESTASINYA DALAM DEBAT POLITIK KAJIAN KASUS DEBAT PEMILIHAN GUBERNUR SUMATERA UTARA 2024 - Harahap, Azrai; Abdullah, Abdullah (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2025)
Mujadalah or argumentative dialogue contained in the Qur'an, is a method of communication that emphasizes ethics, rationality, and respect for the interlocutor. Mujlà principles, such as the use of solid arguments, avoiding personal attacks, and emphasizing wisdom, are important foundations in building constructive communication. This study aims to examine the principles of mujlà in the Qur'an and their application in the context of political debate, especially in the debate for the 2024 North Sumatra governor election. The method used in this study is qualitative with a content analysis approach to debate recordings, related documents, and interpretation of the Qur'an. The findings of the study show that most of the principles of mujlà contained in the Qur'an are reflected in the debate, although there are some violations, such as the use of emotional rhetoric that is not supported by data. This study concludes that the application of the principle of mujlà in political debate can improve the quality of public discussion, strengthen people's political literacy, and create a more peaceful election atmosphere. Therefore, it is highly recommended to integrate mujlà values in future political debate training.